Enhancing Antitumor Efficacy by Simultaneous ATP‐Responsive Chemodrug Release and Cancer Cell Sensitization Based on a Smart Nanoagent. Issue 12 (26th October 2018) - Song, Xiao‐Rong; Li, Shi‐Hua; Guo, Hanhan; You, Wenwu; Tu, Datao; Li, Juan; Lu, Chun‐Hua; Yang, Huang‐Hao; Chen, Xueyuan
Abstract: The exploitation of smart nanoagents based drug delivery systems (DDSs) has proven to be a promising strategy for fighting cancers. Hitherto, such nanoagents still face challenges associated with their complicated synthesis, insufficient drug release in tumors, and low cancer cell chemosensitivity. Here, the engineering of an adenosine triphosphate (ATP)‐activatable nanoagent is demonstrated based on self‐assembled quantum dots‐phenolic nanoclusters to circumvent such challenges. The smart nanoagent constructed through a one‐step assembly not only has high drug loading and low cytotoxicity to normal cells, but also enables ATP‐activated disassembly and controlled drug delivery in cancer cells. Particularly, the nanoagent can induce cell ATP depletion and increase cell chemosensitivity for significantly enhanced cancer chemotherapy. Systematic in vitro and in vivo studies further reveal the capabilities of the nanoagent for intracellular ATP imaging, high tumor accumulation, and eventual body clearance. As a result, the presented multifunctional smart nanoagent shows enhanced antitumor efficacy by simultaneous ATP‐responsive chemodrug release and cancer cell sensitization. These findings offer new insights toward the design of smart nanoagents for improved cancer therapeutics. Abstract : Superior antitumor therapy is demonstrated by simultaneous adenosine triphosphate (ATP)‐responsive chemodrug release and cancer cell sensitization based on a quantum dots‐phenolic nanoagent. The nanoagent constructed through one‐step assembly features high drug loading capacity, ATP‐activated chemodrug delivery, ATP depletion induced cancer cell sensitization, tumor accumulation, and eventual body clearance. Therefore, complete inhibition of tumor growth can be achieved without causing any side effects.